2011
DOI: 10.1016/j.bbamem.2010.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The resurgence of A2B adenosine receptor signaling

Abstract: Since its discovery as a low-affinity adenosine receptor (AR), the A2B receptor (A2BAR), has proven enigmatic in its function. The previous discovery of the A2AAR, which shares many similarities with the A2BAR but demonstrates significantly greater affinity for its endogenous ligand, led to the original perception that the A2BAR was not of substantial physiologic relevance. In addition, lack of specific pharmacological agents targeting the A2BAR made its initial characterization challenging. However, the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 146 publications
(169 citation statements)
references
References 155 publications
10
158
0
1
Order By: Relevance
“…As first step, we induced diabetic nephropathy in previously described Adora2b 2/2 mice. 23,[28][29][30][31][48][49][50][51] Similar to the preceding studies in Cd73 2/2 mice, we observed a more severe degree of diabetic nephropathy in Adora2b 2/2 mice without differences regarding systolic BP and blood glucose levels (Supplemental Figure 4, A and B), but a more severe degree of body weight loss ( Figure 5A), increased kidney weight (Figure 5B), and elevated urine (Figure 5C) and drinking ( Figure 5D) volumes. Determination of the GFR showed a more severe hyperfiltration in Adora2b 2/2 mice compared with diabetic control mice ( Figure 5E).…”
Section: Diabetic Nephropathy Is More Severe In Adora2bsupporting
confidence: 73%
“…As first step, we induced diabetic nephropathy in previously described Adora2b 2/2 mice. 23,[28][29][30][31][48][49][50][51] Similar to the preceding studies in Cd73 2/2 mice, we observed a more severe degree of diabetic nephropathy in Adora2b 2/2 mice without differences regarding systolic BP and blood glucose levels (Supplemental Figure 4, A and B), but a more severe degree of body weight loss ( Figure 5A), increased kidney weight (Figure 5B), and elevated urine (Figure 5C) and drinking ( Figure 5D) volumes. Determination of the GFR showed a more severe hyperfiltration in Adora2b 2/2 mice compared with diabetic control mice ( Figure 5E).…”
Section: Diabetic Nephropathy Is More Severe In Adora2bsupporting
confidence: 73%
“…Thus, the present findings demonstrating that dipyridamole-mediated kidney protection is predominantly mediated by Adora2b expressed on vascular endothelia are somewhat surprising. This could - at least in partbe related to the fact that the Adora2b is the most insensitive AR, requiring adenosine concentrations in the micromolar range (57,58), whereas activation of Adora1a or Adora2a occurs at much lower adenosine concentrations. It is conceivable that particularly experimental conditions such as Ent1 inhibition or deletion during AKI are associated with elevations in extracellular adenosine sufficient to activate Adora2b.…”
Section: Discussionmentioning
confidence: 99%
“…We provide evidence that the A2B receptor is involved in the regulation of compensatory proliferation shortly after amputation, and this correlates with findings in A2B receptor physiology [59]. Indeed, it has been shown that A2B receptor expression is induced by hypoxia and that A2B signalling plays a tissue protective role in many models [60].…”
Section: Discussionsupporting
confidence: 66%